Isoniazid inhibition of mycolic acid synthesis by cell extracts of sensitive and resistant strains of Mycobacterium aurum. - Quémard, A (1991)
Isonicotinic acid hydrazide (isoniazid; INH) inhibition of mycolic acid synthesis was studied by using cell extracts from both INH-sensitive and -resistant strains of Mycobacterium aurum. The cell extract of the INH-sensitive strain was inhibited by INH, while the preparation from the INH-resistant strain was not. This showed that the INH resistance of mycolic acid synthesis was not due to a difference in drug uptake or the level of peroxidase activity (similar in both extracts). As INH did not induce accumulation of any labeled intermediates, it is postulated that the drug acts either on production of labeled chain elongation precursors of mycolic acids or an early step of this elongation. The level of inhibition was not changed by addition of NAD or nicotinamide; thus, INH does not act on mycolic acid synthesis as an NAD antimetabolite. Benzoic or acetic acid hydrazides and known or postulated metabolites of INH (i.e., the corresponding acid, aldehyde, or alcohol) were not inhibitors of cell-free mycolic acid synthesis; the complete structure of INH was required, as already known for inhibition of mycobacterial culture growth. Extracts prepared from INH-treated cells showed reduced mycolic acid synthesis, and the inhibition level was not modified by either extensive dialysis or pyridoxal phosphate. This latter molecule efficiently antagonized INH action by reacting rapidly with INH, as shown by differential spectroscopy. Moreover, pyridoxal phosphate did not release inhibition of INH-treated extracts. It is proposed that INH may covalently react with an essential component of the mycolic acid synthesis system.